Microsatellite Organization in the Grasshopper Abracris flavolineata (Orthoptera: Acrididae) Revealed by FISH Mapping: Remarkable Spreading in the A and B Chromosomes - Milani, Diogo [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP] (Public Library Science, 2014)
With the aim of acquiring deeper knowledge about repetitive DNAs chromosomal organization in grasshoppers, we used fluorescent in situ hybridization (FISH) to map the distribution of 16 microsatellite repeats, including mono-, di-, tri- and tetra-nucleotides, in the chromosomes of the species Abracris flavolineata (Acrididae), which harbors B chromosome. FISH revealed two main patterns: (i) exclusively scattered signals, and (ii) scattered and specific signals, forming evident blocks. The enrichment was observed in both euchromatic and heterochromatic areas and only the motif (C)(30) was absent in heterochromatin. The A and B chromosomes were enriched with all the elements that were mapped, being observed in the B chromosome more distinctive blocks for (GA)(15) and (GAG)(10). For A complement distinctive blocks were noticed for (A)(30), (CA)(15), (CG)(15), (GA)(15), (CAC)(10), (CAA)(10), (CGG)(10), (GAA)(10), (GAC)(10) and (GATA)(8). These results revealed an intense spreading of microsatellites in the A. flavolineata genome that was independent of the A+T or G+C enrichment in the repeats. The data indicate that the microsatellites compose the B chromosome and could be involved in the evolution of this element in this species, although no specific relationship with any A chromosome was observed to discuss about its origin. The systematic analysis presented here contributes to the knowledge of repetitive DNA chromosomal organization among grasshoppers including the B chromosomes.